The mouse and human genes encoding the recognition component of the N-end rule pathway - Kwon, Yong Tae (The National Academy of Sciences, 1998)
The N-end rule relates the in vivo half-life of a protein to the identity of its N-terminal residue. The N-end rule pathway is one proteolytic pathway of the ubiquitin system. The recognition component of this pathway, called N-recognin or E3, binds to a destabilizing N-terminal residue of a substrate protein and participates in the formation of a substrate-linked multiubiquitin chain. We report the cloning of the mouse and human Ubr1 cDNAs and genes that encode a mammalian N-recognin called E3α. Mouse UBR1p (E3α) is a 1,757-residue (200-kDa) protein that contains regions of sequence similarity to the 225-kDa Ubr1p of the yeast Saccharomyces cerevisiae. Mouse and human UBR1p have apparent homologs in other eukaryotes as well, thus defining a distinct family of proteins, the UBR family. The residues essential for substrate recognition by the yeast Ubr1p are conserved in the mouse UBR1p. The regions of similarity among the UBR family members include a putative zinc finger and RING-H2 finger, another zinc-binding domain. Ubr1 is located in the middle of mouse chromosome 2 and in the syntenic 15q15-q21.1 region of human chromosome 15. Mouse Ubr1 spans ≈120 kilobases of genomic DNA and contains ≈50 exons. Ubr1 is ubiquitously expressed in adults, with skeletal muscle and heart being the sites of highest expression. In mouse embryos, the Ubr1 expression is highest in the branchial arches and in the tail and limb buds. The cloning of Ubr1 makes possible the construction of Ubr1-lacking mouse strains, a prerequisite for the functional understanding of the mammalian N-end rule pathway.